2021
DOI: 10.3389/fimmu.2021.650200
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Producing ILCs: Molecular Mechanisms and Disease Relevance

Abstract: Innate lymphoid cells (ILCs) are mainly composed of natural killer (NK) cells and helper-like lymphoid cells, which play a vital role in maintaining tissue homeostasis, enhancing adaptive immunity and regulating tissue inflammation. Alteration of the distribution and function of ILCs subgroups are closely related to the pathogenesis of inflammatory diseases and cancers. Interleukin-10 (IL-10) is a highly pleiotropic cytokine, and can be secreted by several cell types, among of which ILCs are recently verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 99 publications
1
30
0
Order By: Relevance
“…IL1β, TNF‐α, IL6, CRP, and LPS can activate the immune system, while IL10 is an important multifunctional antiinflammatory cytokine. IL10 inhibits leukocyte activation and function, thus inhibiting increases in the levels of inflammatory cytokines, preventing host damage and maintaining the integrity of tissue function (Sun, Wu, Zhang, & Ni, 2021). Paeoniflorin has an antiinflammatory effect, as it reduces the levels of inflammatory factors in the spinal cord (Liu et al, 2020; J. Zhou et al, 2016, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…IL1β, TNF‐α, IL6, CRP, and LPS can activate the immune system, while IL10 is an important multifunctional antiinflammatory cytokine. IL10 inhibits leukocyte activation and function, thus inhibiting increases in the levels of inflammatory cytokines, preventing host damage and maintaining the integrity of tissue function (Sun, Wu, Zhang, & Ni, 2021). Paeoniflorin has an antiinflammatory effect, as it reduces the levels of inflammatory factors in the spinal cord (Liu et al, 2020; J. Zhou et al, 2016, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, TSLP; and IL- 9 activate STAT5 and induce ILC2 survival. IL-4, IL-9, and IL-10 also work on ILC2s in an autocrine manner to maintain cytokine secretion, forming a positive feedback loop ( 193 195 ).…”
Section: The Crosstalk Of Immune Cells In Csumentioning
confidence: 99%
“…IL-10 is an antiinflammatory cytokine secreted by multiple cell types, including monocytes, regulatory T cells, effector T H 1 and T H 2 cells, and innate lymphoid cells. 87,88 It inhibits antigen presentation and proinflammatory cytokine secretion from monocytes and dendritic cells by reducing MHC class II expression and restrains T-cell activation, 87,88 in part through upregulating expression of the suppressor of cytokine signaling protein 3, which inhibits CD8 1 T-cell proliferation. 89 Many studies have identified an association between IL-10 levels and severe COVID-19, 5,70,72,77,79,90 a finding also seen in patients and mouse models of other viral infections, such as influenza and respiratory syncytial virus.…”
Section: Cytokines As Predictors Of Covid-19 Outcomesmentioning
confidence: 99%